2020
DOI: 10.3390/cancers12071846
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment of TERT mRNA Expression across a Large Cohort of Benign and Malignant Thyroid Tumours

Abstract: The presence of TERT promoter (TERTp) mutations in thyroid cancer have been associated with worse prognosis features, whereas the extent and meaning of the expression and activation of TERT in thyroid tumours is still largely unknown. We analysed frozen samples from a series of benign and malignant thyroid tumours, displaying non-aggressive features and low mutational burden in order to evaluate the presence of TERTp mutations and TERT mRNA expression in these settings. In this series, TERTp mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…The high percentage of clinically aggressive tumours that we observed showed promoter methylation, but the absence of promoter mutations (60%, 12/20) denotes the limited prognostic predictive value of testing only TERT promoter mutations, which is in consonance with previous studies 17,46 . On the other hand, tumour‐lymphocytic infiltrates could lead to a misinterpretation of TERT expression results in some particular cases, as this cell lineage can maintain TERT expression after differentiation 20 . In fact, this feature could explain the positivity of TERT expression of most of the tumours in our series with an exceptional response to primary treatment, and without other molecular or clinical evidence related to poor prognosis.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The high percentage of clinically aggressive tumours that we observed showed promoter methylation, but the absence of promoter mutations (60%, 12/20) denotes the limited prognostic predictive value of testing only TERT promoter mutations, which is in consonance with previous studies 17,46 . On the other hand, tumour‐lymphocytic infiltrates could lead to a misinterpretation of TERT expression results in some particular cases, as this cell lineage can maintain TERT expression after differentiation 20 . In fact, this feature could explain the positivity of TERT expression of most of the tumours in our series with an exceptional response to primary treatment, and without other molecular or clinical evidence related to poor prognosis.…”
Section: Discussionsupporting
confidence: 87%
“…17,46 On the other hand, tumour-lymphocytic infiltrates could lead to a misinterpretation of TERT expression results in some particular cases, as this cell lineage can maintain TERT expression after differentiation. 20 In fact, this feature could explain the positivity of TERT expression of most of the tumours in our series with an exceptional response to primary treatment, and without other molecular or clinical evidence related to poor prognosis. Thus, our results underscore the need to consider TERT promoter methylation in screening tools for the stratification of thyroid tumours according to their malignant potential and to report TERT gene expression results along with tumour cellular composition.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…They are known as effective risk factors for patients with PTC. Several investigators have shown that TERT promoter mutations are significantly more common among older patients, bigger tumor size, more aggressive subtype, tumors with extrathyroidal invasion, distant metastasis or higher stage at diagnosis, and are related to poor outcomes [7,[23][24][25][26][27][28]. In addition, Xing et al reported that coexisting BRAF V600E and TERT promoter mutations represented a strong predictor for the most aggressive PTCs with the highest recurrence rate [29].…”
Section: Discussionmentioning
confidence: 99%
“…As an aggressive marker, the BRAF-V600E mutation was less frequently detected in PTC patients concurrent with HT than non-HT ( 15 ). The mRNAs have exhibited a great potential in both physiological and pathological processes of PTC ( 16 18 ). Thus, dysregulated expression mRNAs may be a promising predictor of poor prognosis in PTC.…”
Section: Introductionmentioning
confidence: 99%